The prevalence, variety and impact of wrist problems in elite professional golfers on the European Tour - Hawkes, Roger (BMJ Publishing Group, 2013)
OBJECTIVES: Golf is a popular sport played by an estimated 57 million people. Previous studies on wrist injuries in elite golfers have been of simple design and have demonstrated such injuries to be frequent, although no studies report the incidence, variety, severity or impact on the activity of wrist injuries in detail. This prospective cross-sectional study assesses these factors in a cohort of elite professional golfers. METHODS: European Tour golfers eligible to compete at the 2009 BMW PGA Championship at Wentworth were studied. Study design involved the completion of a structured questionnaire supplemented by interview and examination when required, with performance statistics provided by the European Tour. The severity of injury was assessed by the number of missed tournaments and the amount of time of missed practice. RESULTS: 128 of 153 eligible golfers, (84%) completed the study with 38 golfers (30%) reporting 43 problems. The majority of injuries (67%) occurred in the leading wrist at the most common location, the ulnar side of the wrist (35%). 87% of all ulnar-sided and 100% of radial-sided problems were in the leading wrist. CONCLUSIONS: There were clear side differences reported by the players with the lead wrist demonstrating much higher injury rates in all areas. The most significant injury, in terms of absence from competition, was extensor carpi ulnaris tendon subluxation. Specific injuries are explained in relation to the biomechanics of the golf swing. Most structural injuries have a specific treatment and rehabilitation plan, which can involve significant periods of time away from the sport, while the management of many of the more minor problems is through alterations in technique or practice regimes, aiming to keep a golfer playing during recovery.